Generative AI and the Scope of EU Copyright Law: A Doctrinal Analysis in Light of the Referral in Like Company v. Google - Tim W. Dornis; Nicola Lucchi (IIC - International Review of Intellectual Property and Competition Law, 2025)
This article offers a doctrinal analysis of the copyright implications raised by Like Company v. Google Ireland (C-250/25), the first case to bring generative AI before the Court of Justice of the European Union. It examines whether the training and output of systems like Gemini infringe exclusive rights under EU copyright law. We argue that AI model training may involve acts of reproduction under Art. 2 of the InfoSoc Directive, while the dissemination of AI-generated outputs, especially through public interfaces, may trigger the right of communication to the public under Art. 3. Particular concerns arise when protected content is recognisably reproduced or when AI outputs serve as functional substitutes for original works, thereby affecting the normal exploitation of those works. While not a formal infringement criterion, such functional substitution is relevant in assessing the application of exceptions and compliance with the three-step test. The paper also challenges the applicability of the text and data mining exception to generative uses, highlighting its incompatibility with the limitations imposed by the three-step test. Ultimately, the analysis supports a technologically neutral, rights-based interpretation that safeguards the economic viability of creative production in the algorithmic age.
Keywords: 340; Artificial intelligence; Model training; Copyright; Generative AI